Artificial covering on trap nests improves the colonization of trap-nesting wasps - Taki, Hisatomo; Kevan, Peter G; Viana, Blandina F; Silva, Fabiana O; Buck, Matthias (Journal of applied entomology (1986), 2008)
To evaluate the role that a trap-nest cover might have on sampling methodologies, the abundance of each species of trap-nesting Hymenoptera and the parasitism rate in a Canadian forest were compared between artificially covered and uncovered traps. Of trap tubes exposed at eight forest sites in six trap-nest boxes, 531 trap tubes were occupied and 1216 individuals of 12 wasp species of four predatory families, Vespidae (Eumeninae), Crabronidae, Sphecidae and Pompilidae emerged over 2 years, and no bee species were found. Results indicated that artificial covering led to a significant increase in the number of nested tubes of Ancistrocerus adiabatus, Ancistrocerus antilope, Ancistrocerus campestris and Auplopus mellipes, and significant effects of covering were not found for the other species. No significant difference in the overall parasitism rate between covered and uncovered traps was noted. These suggested that the covering technique could provide more opportunities for some wasp species to colonize trap nests.